Dinamika Hukum Adat dan Islam terhadap Pernikahan Mendahului Kakak Kandung - Siska Ayu Anggraini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Marriage that precedes a sibling is a social phenomenon that often triggers differing views between customary law and Islamic law in Indonesian society. This study aims to examine the perspectives of customary law and Islamic law on this phenomenon and understand the dynamics of the interaction between these two legal systems. The research adopts a qualitative approach with a descriptive-analytical design, combining primary data from in-depth interviews with customary leaders, religious scholars, and marriage participants, along with secondary data from relevant literature. The results show that customary law tends to regulate the order of marriage within the family, with social sanctions for violations, while Islamic law does not have such prohibitions and emphasizes individual freedom as long as the marriage requirements are fulfilled. Despite the potential for conflict, integration between customary law and Islamic law is possible through a dialogical approach involving all relevant parties. This study recommends strengthening dialogue between customary leaders and religious scholars to create harmony in marriage practices within the community and encourages further research to gain a broader understanding of public perceptions on this issue.